Pattern of outcome of management of bipolar-1 disorder in manic phase during hospital stay: a case series - Algin, Sultana; Akter, Asha; Tanzilla, Nusrat Jahan (BIRDEM Medical Journal, 2023)
Background: Most of the unmanageable patients of bipolar-1 disorder need hospital admission during manic episode. Pharmacological management is challenging because of severity of condition, presence of co-morbidity, need for poly-pharmacy, side effects of medication etc. The purpose of this article is to evaluate the treatment pattern of hospitalized bipolar-1 manic patients and effectiveness of drug combinations in controlling manic symptoms and reducing hospital stay. Methods: This is a case series on 7 admitted bipolar-1 manic patients, who were treated within last 6 months at Department of Psychiatry, BSMMU. Young Mania Rating Scale (Y-MRS) was applied just after admission and before discharge. All patients were given psycho-education and follow up plan. Results: Average hospital stay was around 30 days (maximum 73 days and minimum 7 days). Based on Y-MRS score, 2 cases were found to have severe symptom, other 5 cases were categorized as having moderate symptoms on admission. The score on discharge showed that all patients achieved remission from acute symptoms. Patient with first/second episode, younger age with no family history of mental illness tend to respond better with single agent (first/second generation antipsychotic) with less hospital stay. Patient with multiple episodes, history of non-compliance and positive family history were correlated to severe episode, need for polypharmacy and had prolonged hospital stay. Conclusion: Treatment of acute mania should be personalized in respect to several clinical criteria, which include manic symptoms, course specifiers and patient factors. BIRDEM Med J 2023; 13(2): 103-106